Atlas Makerspaces in Public Libraries in The Netherlands - Caso, Olindo (2019)
Public libraries want to contribute to an inclusive and innovative society and aim to enable their patrons to acquire the necessary 21st century skills. Dutch public libraries are therefore gradually adding more and more activities to their curriculum, teaching these different types of skills, such as 'invention literacy'. They also often provide a 'performative space' (i.e. a makerspace) for their patrons. This means library spaces are no longer dominated by books, but rather reflect the current development in libraries' core business, moving from collections to connections in order to serve their local communities. The KB, the National Library of The Netherlands, participated in the KIEM1 project Performative Spaces in Dutch Public Libraries. Stepping Stones of Inclusive Innovation, researching the development of performative spaces in libraries. This project, a collaboration with the Faculty of Architecture and the Built Environment at the Delft University of Technology, fits the KBs strategic interests in providing an innovative and socially aware library system.